Analysis of the Pedagogical Competence Development of Madrasah Teachers in Serang Regency - Rohimat, Sonny; Apud, Apud; Mu'awanah, Uyu; Nadhirah, Yahdinil Firda; Fitriani, Dini (Universitas Muhammadiyah Mataram, 2026)
The quality of education in Islamic schools (madrasah) is highly dependent on teachers' pedagogical competence, which is a core skill in managing student-centred teaching and learning processes. However, the implementation of this competence development has not been internalized regularly. This study aims to identify and analyze the forms of pedagogical competence development activities and their supporting and inhibiting factors for Islamic school teachers in Serang Regency. This study employs a descriptive qualitative approach via a structured survey of teachers at eight private Madrasah Tsanawiyah in Serang Regency, utilizing convenience sampling to gather both quantitative metrics and qualitative narratives. Data collected on the frequency, types, and organizers of competency development were processed through systematic data reduction and synthesis to provide a comprehensive analysis of teacher pedagogical growth. The results showed that the majority of teachers (68.9%) rarely participated in competence development activities, with the main obstacles being adjustments to teaching schedules and budget constraints. The most dominant type of activity participated in was training (70.2%), driven by the accessibility of certified independent online training such as PINTAR from the Ministry of Religious Affairs. The most popular topics were curriculum or syllabus development and learning design, with the main organizers being schools or foundations and the Ministry of Religious Affairs. Overall, there is a significant gap between teachers' professional awareness and the reality of implementation, which is hampered by issues of time, budget, and lack of frequency of ongoing activities, so that a hybrid, adaptive, and integrated development model is needed in the teacher's workload.